HUBUNGAN PERSEPSI DAN SIKAP MASYARAKAT TERHADAP PENDERITA GANGGUAN JIWA DI DESA TELUK KENIDAI KECAMATAN TAMBANG KABUPATEN KAMPAR - Indah Purnama Sari; Fathra Annis Nauli; Febriana Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Mental disorder is a change in mental function that causes individuals to suffer from the disorder and difficult to carryout societal roles. This study aims to determine the relationship between perception with public attitudes toward peoplewith mental disorders in the village of Teluk Kenidai. This is descriptive correlation study with Cross Sectionalapproach. The sample in this research is 71 respondents taken based on the criteria of inclusion by using TotalSampling technique. The measuring tool used is a questionnaire that has been tested for validity and reliability. Dataanalysis using Chi-Square test. The results show that the value of p value = 0.018 (p <0.05), which means there is asignificant relationship between perceptions with the attitude of society against mental disorders. This research can beused as a foundation of information and increase the insight of the community against individuals who have mentaldisorders. His recommended that society can change negative perception and attitude to be positive.Key words : Attitude,mental disorder, perception,